2020
DOI: 10.1515/mammalia-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: natural or anthropic origin?

Abstract: AbstractViruses similar to the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have been discovered in bats of the genus Rhinolophus and in the Sunda pangolin, Manis javanica Desmarest, 1822, suggesting that these animals have played a key role in the emergence of the Covid-19 outbreak in the city of Wuhan, China. In this paper, we review the available data for sarbecoviruses (viruses related to SARS-CoV [2002–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 29 publications
4
43
0
1
Order By: Relevance
“…Further substantiating this hypothesis, the geographic distribution of Manis javanica [28] overlaps the ecological niche here predicted for bat SARS-CoV-2 viruses (Figures 4a and 4b), and SARS-CoV-2 neutralizing antibodies have been recently detected in a Sunda pangolin collected in eastern Thailand [8]. Collectively, these data strengthen the hypothesis that pangolin trafficking is responsible for multiple exports of SARS-CoV-2-like viruses to China [3].…”
Section: Pangolins Contaminated By Bats In Southeast Asiasupporting
confidence: 74%
See 3 more Smart Citations
“…Further substantiating this hypothesis, the geographic distribution of Manis javanica [28] overlaps the ecological niche here predicted for bat SARS-CoV-2 viruses (Figures 4a and 4b), and SARS-CoV-2 neutralizing antibodies have been recently detected in a Sunda pangolin collected in eastern Thailand [8]. Collectively, these data strengthen the hypothesis that pangolin trafficking is responsible for multiple exports of SARS-CoV-2-like viruses to China [3].…”
Section: Pangolins Contaminated By Bats In Southeast Asiasupporting
confidence: 74%
“…More recently, several viruses showing between 96.2 and 91.8 % of genome identity with SARS-CoV-2 were identified from fecal samples of four horseshoe bat species: the RaTG13 virus was isolated from a Rhinolophus affinis bat collected in Yunnan in 2013 [1]; the RmYN02 virus was found in a Rhinolophus malayanus bat sampled in Yunnan in 2019 [6]; two variants of the same virus RshSTT200 (other variant: RshSTT182) were detected in two Rhinolophus shameli bats caught in northern Cambodia in 2010 [7]; and five variants of the same virus RacCS203 (other variants: RacCS224, RacCS253, RacCS264, and RacCS271) were sequenced from five Rhinolophus acuminatus bats collected in eastern Thailand in 2020 [8]. These data confirmed that the genus Rhinolophus is the natural reservoir host of all viruses of the subgenus Sarbecovirus [3,5]. The bat species Rhinolophus acuminatus and Rhinolophus shameli are endemic to Southeast Asia whereas the two other bat species, Rhinolophus affinis and Rhinolophus malayanus, are distributed in both Southeast Asia and China ( Figure 1), suggesting that Southeast Asia is the main region where bat SARS-CoV-2-like viruses diversified.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Many authors argue that humans favored this pandemic, because anthropogenic activities enhance conditions to cross the species barrier from wild animals to humans ( Hassanin et al, 2020 , Volpato et al, 2020 ). The main causes were encroaching into natural areas, the increased demand and market of bushmeat and, a synergy with globalization that promoted its rapid dissemination ( Volpato et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%